Extraction and deacetylation process of chitosan from Tachypleus gigas horseshoe crab of Balok and Muar, Peninsular Malaysia - Wan Omar, Wan Syazzawani; Kassim, Zaleha; Ramli, Riwan (International Journal of Current Research, 2022)
Background: Chitin and chitosan from the exoskeleton of horseshoe crab was reported to have a comparable quality to commercial chitosan. It would become a good alternative for the existing chitosan in the market. Nonetheless, inefficient isolation processes could lead to a waste to this invaluable raw material and incur additional cost. Chitosan isolated from the raw chitin could be affected by the frequency of deacetylation process. At the same time, horseshoe crabs, as known as a living fossil, must be exploited sustainably. Objective: Thus, it is important to determine if a single deacetylation process can satisfy the quality and amount of extracted chitosan from the exoskeleton. Methods: In this experiment, exoskeletons of horseshoe crab were obtained from two different area (Balok in the South China Sea coast and Muar in the Straits of Malacca) and processed through several steps of grinding, deproteinization and demineralization before went through a single and double process of deacetylation using 50% NaOH. FT-IR spectra were analysed to ensure the completion of deacetylation process. Statistical analysis was done using IBM SPSS Statistics Version 22. The data were presented as mean ± standard deviation (SD). The p value was obtained from the independent-samples T-Test analysis with p < 0.05 was considered significant. Results: Percentage of chitin and chitosan isolated does not have a significant difference (p>0.05) between Balok and Muar. Nonetheless, the degree of deacetylation is significantly different (p<0.05) between the study sites despite the insignificant difference between single and double deacetylation processes. Conclusion: The results suggest that a double process of deacetylation would be efficient to produce chitosan from chitin extracted from the horseshoe crab exoskeleton. The yield was significantly higher when using samples from Balok than Muar which could be related to some other factors that should be further investigated.